Structural Changes of Tooth, Root and Root Canal Morphometrics using Conebeam Computed Tomography for Assessment of Age in South Indian Population-A Retrospective Study - Sangavi , R; Saraswathi , G K; Srividhya , S (Journal of Indian Academy of Forensic Medicine, 2023)
The estimation of age has been an antiquated exercise. The tooth with its highly resistant morphometrics provides us with a non-invasive modality to determine the age of the person. The major aim of this current study is to assess the accuracy of a chronological age of an individual by measuring the structural changes of tooth, root and root canal morphometrics, tooth and root length from CBCT images of mandibular right and left 1st premolar. Aretrospective study involving 200 CBCT images between the age of 20–60 years were retrieved from the department database. The samples were further divided into five groups based on their age, each group contains 20 samples. Mandibular 1st premolar on both left and right side were analysed. The structural changes of teeth, attrition, secondary dentine and periodontal recession were graded according to Gustafan’s method, the tooth length and root length were measured. The tooth length and root canal diameter were positively corelated to the chronological age of the patient on right and left side. In multiple regression analysis attrition on right and left side were positively corelated to the chronological age of the patient, secondary dentine and periodontal recession on the right and left side respectively were positively correlating to the chronological age of the patient. The reliability of chronological age estimation using the structural changes of teeth, root and root canal morphometrics provides fairly reliable results. This has resulted in the error of age prediction narrowing down to +/- 1.7 years to 2.35 years.